Stressing out—carp edema virus induces stress and modulates immune response in common carp - Zawisza, Maria; Rebl, Alexander; Teitge, Felix; Krzystyniak, Barbara; Piackova, Veronika; Gela, David; Kocour, Martin; Chadzinska, Magdalena; Adamek, Mikolaj; Rakus, Krzysztof (Frontiers in Immunology, 2024)
Carp edema virus (CEV) is a fish poxvirus that primarily infects the gills of common carp. CEV causes koi sleepy disease (KSD), which is highly contagious and can result in mortality of up to 100 %. In the present study, we analyzed the stress and immune responses during KSD in two strains of common carp with different resistance to CEV: susceptible koi and resistant Amur sazan. Experiments were performed at two temperatures: 12 and 18 °C. In case of koi carp we also analyzed the effect of the supplementation of 0.6 % NaCl into the tank water, which prevents mortality of the CEV-infected fish (salt rescue model). We found that CEV-infected koi kept at 18 °C had the highest viral load, which correlated with the most severe histopathological changes in the gills. CEV infection resulted in the activation of stress response reflected by the up-regulated expression of genes involved in stress response and increased level of cortisol and glucose in the blood plasma. These changes were the most pronounced in CEV-infected koi kept at 18 °C. At both temperatures, the activation of antiviral immune response was observed in koi kept under freshwater and NaCl conditions upon CEV infection. Interestingly, a clear down-regulation of the expression of adaptive immune genes was observed in CEV-infected koi kept under freshwater at 18 °C. Thus, CEV induces a stress response and modulates adaptive immune response in koi and this is correlated with the level of viral load and disease development.